Gastrointestinal differentiation marker Cytokeratin 20 is regulated by homeobox gene CDX1 - Chan, Carol W M; Wong, Newton A; Liu, Ying; Bicknell, David; Turley, Helen; Hollins, Laura; Miller, Crispin J; Wilding, Jennifer L; Bodmer, Walter F (Proceedings of the National Academy of Sciences - PNAS, 2009)
CDX1 is a transcription factor that plays a key role in intestinal development and differentiation. However, the downstream targets of CDX1 are less well defined than those of its close homologue, CDX2. We report here the identification of downstream targets of CDX1 using microarray gene-expression analysis and other approaches. Keratin 20 (KRT20), a member of the intermediate filament and a well-known marker of intestinal differentiation, was initially identified as one of the genes likely to be directly regulated by CDX1. CDX1 and KRT20 mRNA expression were significantly correlated in a panel of 38 colorectal cancer cell lines. Deletion and mutation analysis of the KRT20 promoter showed that the minimum regulatory region for the control of KRT20 expression by CDX1 is within 246 bp upstream of the KRT20 transcription start site. ChIP analysis confirmed that CDX1 binds to the predicted CDX elements in this region of the KRT20 promoter in vivo. In addition, immunohistochemistry showed expression of CDX1 parallels that of KRT20 in the normal crypt, which further supports their close relationship. In summary, our observations strongly imply that KRT20 is directly regulated by CDX1, and therefore suggest a role for CDX1 in maintaining differentiation in intestinal epithelial cells. Because a key feature of the development of a cancer is an unbalanced program of proliferation and differentiation, dysregulation of CDX1 may be an advantage for the development of a colorectal carcinoma. This could, therefore, explain the relatively frequent down regulation of CDX1 in colorectal carcinomas by hypermethylation.